Strategi Guru Pendidikan Agama Islam Membentuk Karakter Religius Peserta Didik di SMP Al Baitul Amien Jember: The Strategy Of Islamic Religious Education Teachers To Form The Religious Character Of Students At SMP Al Baitul Amien Jember - Sahuri, Mohammad Sofiyan (IJIT: Indonesian Journal of Islamic Teaching, 2022)
The problem of moral decline has recently plagued the younger generation. Symptoms can be seen from the outbreak of drug abuse, promiscuity, crime, violence, and other dishonorable behavior. This is inseparable from the rapid development of Science and technology. The effects that have been seen include reduced verbal communication, children tend to be selfish and want instant results without going through the process. Parents, educators, communities, nations, and countries play a role in this improvement. This research uses qualitative design. Data collection techniques using observation, in-depth interviews, and documentation. In this study, the determination of research subjects using purposive techniques. In data collection, this study uses Miles and Huberman's interactive data reduction model, data presentation, and conclusion. In testing the validity of the data, researchers mengguanakan triangulation, source triangulation, triangulation methods, and peer discussion. This study found a variety of related activities, namely the habituation to pray in congregation, planting exemplary, and planting time discipline. Supporting factors consist of internal factors and external factors. In contrast, inhibiting factors consist of lack of capacity, completeness of prayer facilities in mosques, teacher control when performing congregational prayers at home, and lack of understanding of students about the importance of congregational prayers. Problem kemerosotan moral akhir-akhir ini menjangkit generasi muda. Gejalanya terlihat dari merebaknya kasus penyalahgunaan narkoba, pergaulan bebas, kriminalitas, kekerasan, dan perilaku tidak terpuji lainnya. Hal ini tidak lepas dari pesatnya perkembangan ilmu pengetahuan dan teknologi. Dampak yang sudah terlihat antara lain berkurangnya komunikasi secara verbal, anak cenderung egois dan menginginkan hasil serba instan tanpa melalui proses. Orang tua, pendidik, masyarakat, bangsa dan negara berperan dalam pembenahan ini. Penelitian ini menggunakan desain kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara mendalam, dan dokumentasi. Dalam penelitian ini penentuan subjek penelitian menggunakan teknik purposive. Dalam pengumpulan data, penelitian ini menggunakan model interaktif Miles dan Huberman yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Dalam uji keabsahan data, peneliti mengguanakan triangulasi, yaitu triangulasi sumber, triangulasi metode, dan diskusi sejawat. Dalam penelitian ini ditemukan berbagai aktivitas yang berkaitan yaitu pembiasaan sholat berjamaah, penanaman keteladanan, dan penanaman disiplin waktu. Faktor pendukung terdiri dari faktor internal dan faktor eksternal sedangkan faktor penghambat terdiri dari kurangnya kapasitas, fasilitas kelengkapan sholat di masjid dan kontrol guru ketika pelaksanaan sholat berjama’ah di rumah, serta kurangnya pemahaman siswa terhadap pentingnya sholat berjamaah.